A Cointegration Analysis of Treasury Bill Yields - Hall, Anthony D.; Anderson, Heather M.; Granger, Clive W. J. (The Review of Economics and Statistics, 1992)
This paper shows that yields to maturity of U.S. Treasury bills are cointegrated, and that during periods when the Federal Reserve specifically targeted short-term interest rates, the spreads between yields of different maturity define the cointegrating vectors.This cointegrating relationship implies that a single non-stationary common factor underlies the time series behavior of each yield to maturity and that risk premia are stationary.An error correction model which uses spreads as Ihe error correction terms is unstable over the Federal Reserve's policy regime changes, but a model using post 1982 data is stable and is shown to be useful for forecasting changes in yields.